Livable human communities: A sustainability narrative - Cotner Douglas M. (Spatium, 2009)
This paper will explore the subject of “Livable Human Communities” as the product of “Sustainable Development”, which is rooted in the “Science of Sustainability”. Public policy to facilitate Livable Human Communities will also be examined, with recommendations proffered, which are science based, within the context of a sustainable development paradigm, which is reliant upon the “Ecological Footprint” and “A Unified Field Theory of Adapted Space”, for policy formation purposes.